Feromônios de insetos: tecnologia e desafios para uma agricultura competitiva no Brasil - Lima, Eraldo R.; Zarbin, Paulo H. G.; Rodrigues, Mauro A. C. M. (Química Nova, 2009)
Pheromones are chemical compounds used by species to communicate intra and inter specifically. As strategy of integrated pest management (IPM), the use of these compounds allows the monitoring of target insects that results in more reliable interventions and consequently avoiding unnecessary use of pesticides. In certain crops these compounds are used as a control measure, not only monitoring. The Brazilian agriculture has a portfolio of 49 major crops that are attacked by 447 species of insects. Of this total, 103 species have already been the subject of study in the research with pheromones. Currently, in the Brazilian market, 28 pheromone products are indicated for the control of 19 insect pests. However, these products are not used regularly in major crops of the country. This stems from the lack of implementation of IPM of these crops. While the research focused on the main species of agribusiness pests, marked of pheromones products is serving to more marginal crops like apples and peaches at the expense of major crops like soybean and corn.
Keywords: Pheromones; Brazilian agriculture; Pest control